Critical Reflection on the Empty Box Phenomenon and Political Party Cadre Crisis - Sudiarsana, I Kadek; Fithrian Luthfan, Gusti Fadhil; Tombi, Johan Tri Noval Hendrian (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Indonesia's democratic life in the 2024 elections is characterized by complex dynamics, such as demonstrations against the alleged constitutional disobedience by the Baleg DPR and the empty box phenomenon in 37 regions. This indicates the degradation of the quality of democracy, where political parties that should be a forum for political education are instead shackled by the hegemony of fat coalitions, ignoring the function of regeneration. This normative juridical research uses statutory and conceptual approaches, with qualitative data analysis, concluding that parties fail to optimize their strategic role in democracy. The empty box phenomenon reflects the pragmatism of political parties that are trapped in the comfort zone of coalitions, even losing the basic philosophy of their establishment. The implications include election budget inefficiency, inhibition of regional strategic programs due to risk-averse acting regional heads, and threats to the quality of development. To restore democracy, the author proposes: (1) limiting political party coalitions, (2) reformulating the requirements for independent pathways in regional elections, and (3) preventing power domination in order to create a competitive democratic ecosystem with integrity.